The Party of Costa Rica in a Strange Land: Narrations of the Celebration of Independence in the City of Limón Through the Written Press (1885-1921) - Ordoñez Cash, Fernando (2022)
During the established period, the region and later city of Limón became a diverse socio-cultural area due to the heterogeneous migration that populated their lands. It caused that the celebration of the independence of Costa Rica, in its «Limonense» variant, was different from the one celebrated in the main cities of the Central Valley. The written press releases that are presented below give a sample of how this national holiday was celebrated by the city of Limón and of the rejection speeches —from the Central Valley— towards Limón, its inhabitants and how they celebrated the festival.